(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Human demands are rising day by day as a result of the growing population. Simultaneously, the need for food materials is growing. In order to satisfy food demand, crop production efficiency must be improved in situations when labour and water are scarce. The necessity of the time is to make effective use of existing labour, water, and fertilisers in order to reduce the cost of yearly crop production. Luckily, technology today as well as practices may help you achieve your cost-cutting and quality-control goals. This preliminary research focuses on a low-cost automated smart irrigation system that conserves water and human labour while providing the desired quantity and quality of crops. The suggested system also includes a basic yet compact smart phone application that allows the farmer to carry out watering and fertilisation regimens. The experimental setup at the farm measuring 1 acre of sugarcane production demonstrated a 56 percent decrease decrease in water consumption, a 90 % decrease in labor expenditures for irrigation, and a 75 percent reduction in power consumption when compared to the conventional procedures. As a consequence, the proposed strategy produces a win-win situation for both farmers and the government, which is currently competing for water and power in our country.